MyoD expression in the forming somites is an early response to mesoderm induction in Xenopus embryos. - Hopwood, N D (1989)
We describe the cloning, cDNA sequence and embryonic expression of a Xenopus homologue of MyoD, a mouse gene encoding a DNA-binding protein that can activate muscle gene expression in cultured cells. The predicted Xenopus MyoD protein sequence is remarkably similar to mouse MyoD. Zygotic expression of MyoD begins in early gastrulae, but there is a low level of unlocalized maternal message. Northern blot analysis of dissected embryos and in situ hybridization show that MyoD RNA is restricted to the gastrula mesoderm and to the somites of neurulae and tailbud embryos. The time and place of MyoD expression are consistent with a role for MyoD in the activation of other muscle genes in the somites of the frog embryo. However, MyoD is skeletal muscle-specific and is not expressed even in the early embryonic heart, which co-expresses cardiac and skeletal actin isoforms. Striated muscle genes can therefore be activated in some embryonic tissues in the absence of MyoD. The concentration of MyoD in the somites falls once they have formed, suggesting that MyoD may act there transiently to establish muscle gene expression. MyoD transcription is activated following mesoderm induction, and is the earliest muscle-specific response to mesoderm-inducing factors so far described.